Taylor collocation method for high-order neutral delay Volterra integro-differential equations - Laib, Hafida; Bellour, Azzeddine; Boulmerka, Aissa (Journal of Innovative Applied Mathematics and Computational Sciences, 2022)
In this paper, the Taylor collocation method is applied to numerically solve a kth-order neutral linear Volterra integro-differential equation with constant delay and variable coefficients. We also provide a rigorous analysis to estimate the difference between the exact and approximate solution and their derivatives up to order k-1. Numerical examples are included to prove the performance of the presented convergent algorithm.